The middle class and economic reforms - Lahiri, Ashok K. (2014)
The middle class is the basis of a strong and functional democracy. Indian economic policy has, in the past, focused almost entirely on the poor, but the end of poverty lies in the production of the middle class, one that would include many of those who are currently among the poor. This article offers a strategy that takes us away from an economy split between the poor and the rich, and from a charitable notion of economic redistribution to the possibility of rights-based claims for economic justice. - Reproduced.
Keywords: Middle class; Economic reform